Designing a Sustainable Energy System for a Nut Processing Plant in Mozambique - Davidsson, Felix; Busse, Rasmus (My University, 2023)
Abstract Mozambique is one of the least developed countries in the world, where only a few percent of the rural population have access to electricity, and those who have access face substandard service as the grid is prone to outages. This project is done in collaboration with a company in Mozambique that harvests macadamia nuts and wants to process them to increase their value. The company has its plantation in the rural areas of northern Mozambique, Niassa province, and plans to build a processing plant and have sustainable, on-site, energy generation to supply demand. The aim of this report is to investigate how the energy demands of the processing plant can be met using renewable and sustainable generation technology. This was done by creating a linear cost optimization model in GAMS to determine the energy mix and size of each technology. Different cases were created and evaluated based on different factors such as annual cost, practicality and energy usage. Large economic gains were noticed for grid connected systems and the solutions had cheaper annual costs but were highly dependent on the possibility to sell electricity. If the possibility to sell electricity was removed, but the ability to buy remained, installed generation capacity decreased and more electricity was instead purchased from the grid. Grid connected solutions had no investments in energy storage but to handle outages, it was necessary to have batteries, where outage duration and time of day were deemed most crucial on battery sizing. Variations in solar radiation had a significant effecton off-grid systems while grid connected solutions were barely affected. Based on the observed cases and their results, the energy system with the lowest total annual cost is a grid connected system with solar PV for electricity generation and pyrolysis for heat generation. Unless the grid becomes more reliable or demand side management can be utilized, a battery should be added to ensure processing during outages. For an off-grid solution, the same technologies would be used but the size of the battery should be increased.
Keywords: Africa, biochar, cost optimization, Mozambique, off-grid, outages, pyrolysis, solar, sustainable, waste utilization; Africa; biochar; cost optimization; Mozambique; off-grid; pyrolysis; sustainable; waste utilization